Revealing of Hormonal Characteristics of Phenotype A Polycystic Ovarian Syndrome - Zainab G. Falh; Basil O. Saleh; Afraa M. AL- Naddawi (Diyala Journal of Medicine, 2025)
Background: Phenotype A also referred the classic PCOS phenotype, represents the most severe clinical form as it encompasses all three diagnostic features clinical and/or biochemical hyperandrogenism (HA), ovulatory dysfunction (OD), and polycystic ovarian morphology (PCOM). it is more commonly found in subjects identified in clinical populations. Objectives: To investigate the hormonal changes in phenotype (A) of polycystic ovary syndrome (PCOS). Patients and Methods: This study was carried out at Department of Biochemistry, College of Medicine, University of Baghdad. Investigations included serum measurements of anti-müllerian hormone (AMH), free testosterone, inhibin B, by using enzyme linked immunosorbent assay (ELISA) technique, prolactin, luteinizing hormone (LH), follicle stimulating hormone (FSH) were measured by TOSOH technique. The ratio of LH/FSH was calculated. Results: The mean (±SEM) value of serum free testosterone levels of phenotype (A) PCOS was significantly higher than that of controls (p=0.001). However, the mean (±SEM) value of AMH levels of phenotype (A) PCOS was higher than that of control women, but did not reach the significant level (p=0.06). The mean (±SEM) values of LH levels and LH/FSH ratio, of phenotype (A) PCOS were significantly higher than those of control women (p=0.03, p=0.001, respectively). In addition, significant correlations were observed among the studied hormones in phenotype (A) PCOS. Conclusion: Phenotype A is the predominant one of PCOS phenotypes and is associated with highest serum AMH, free testosterone and obesity. The pattern of hormonal changes and correlations among them may shed light on the new pathophysiology of the phenotype A PCOS and may aid in treatment strategy. Keywords: Anti-müllerian hormone, Free testosterone, Inhibin B, LH/FSH ratio, Polycystic ovary syndrome.